Piggery wastewater characteristics associated with particle size and settling time : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in agricultural engineering at Massey University, Palmerston North, New Zealand - Bruere, Andrew Charles (Massey University, 1988)
Solid-liquid separation is used widely as a waste treatment process. A wide range of solid-liquid separators have been applied to agriculture overseas, but their application in New Zealand has been limited. This study has determined levels of pollution parameters associated with particle size and settling time for wastewater from a New Zealand piggery. This information has been used to compare the effectiveness of sieving and settling on separating solids from piggery wastewaters. It was found that a high proportion (75-90 %) of COD, TS, VS and TP were associated with filtrable solids, and therefore indicate that some form of solid-liquid separation can remove high levels of these parameters. Only low levels of TKN were associated with filtrable solids so their removal by solid-liquid separation is limited. The study revealed that removal of particles in the 500-2000 um range will not remove high levels of COD, TS, VS, TP or TKN and to to remove substantial levels of the first four parameters, particles less than 500 um need to be removed. Settling tests demonstrated that high levels of COD, TS and VS were removed in a short time period (5 minutes), and that substantial levels of all parameters were settled in longer time periods. Comparison of the two trials reveals that very small aperture sieves would be required to achieve a similar removal of all parameters, compared with a five minute sedimentation period. Sedimentation appears to be an effective waste treatment option for piggery wastewater. Further research is required to quantify performance in the field and find practical methods of disposal or utilization for the separated sediment.
Keywords: Swine Housing; Sewage Purification